Money Laundering Procedure - Lewandowska, Karolina (Journal of Finance and Financial Law, 2017)
The aim of the article is to present legislation to prevent the crime of money laundering. Appoint-ing a special financial body called the General Inspector of Financial Information imposes new obligations on financial institutions and provides many criminal sanctions for the violation of regulations. The main aim of this article is to characteristics the process of money laundering, define the process, the recognition of economic, types and methods of money laundering, and also assessment of the scale of the crime and its consequences. Presentation of the legal aspects of money laundering is important. The hypothesis implies a negative effect of money laundering for the economy and market mechanisms aimed at determining market parameters. This procedure affects the economy in a destabilizing way. The consequences of the destabilization are, among others, the increase in the level of corruption in the state, the violation of the principles of fair economic competition, the disruption of the financial system and the development of organized crime. Money laundering has a negative impact on the economies of the world's economies, which hamper the development of state economies. As a result, stronger organized crime groups are emerging, and by combating this process, they can reduce their cash inflows from legitimate sources, reducing their negative impact on the economy of the states.